Avaliação de propriedades criadoras do jacaré-de-papo-amarelo (Caiman latirostris: Alligatoridae) do Estado de São Paulo - Carreira, Laura Borelli Thomaz [UNESP] (2014)
This study evaluated the viability of commercial farms of broad-snouted caiman (Caiman latirostris) in the State of São Paulo, in a farming system. Items of relevance to the cost of the activities, and the parameters related to the profitability and viability of the farming were indentified. In the first case a property was evaluated focusing on the production of meat and skin, where positive values for the net present value (NPV) and internal rate of return (IRR) exceeding 40% were obtained showing a high economic attractiveness. In the second case a property was evaluated with focus on producing matrices and reproducers to be sold to the implantation / renovation of new breeding stocks. In this second case the activity was not economically viable